A framework to support the development of empathic games - Galvão, Vinícius Ferreira; Maciel, Cristiano; Dos Santos Nunes, Eunice Pereira; Da Hora Rodrigues, Kamila Rios (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
A subcategory of games is gaining the attention of the academic community: Empathic Games. Games that forgo some of a game’s pure entertainment value, in favor of allowing the player to experience how it is to be in "someone else’s shoes" and deal with the challenges they face in their daily lives. For example, the daily routine of a doctor, the perspective of a person in a state of grief, how does a person afflicted with a physical disability overcome their limitations etc. There are works in many different areas that highlight the importance of empathy. However, there are very few works detailing how digtal games generate empathy in the user. With this knowledge gap in mind, the present study details the creation of the conceptual framework CERCO (Components, Elements, Requirements, and COncepts) and the following artifacts: glossaries, synthesis of empathic games, historical analysis of the game industry use of empathic elements, design guidelines, and videos. This study sought to create a framework and artifacts to support professionals, of all levels of expertise, during the game-creating process; they constitute the main results of this study and are detailed further on how they can support the creation of empathic games that, via interaction, can be a tool to tackle difficult life subjects via interaction.